(untitled) (Bioagro, 2024)
The objective of this research was to characterize morpho-agronomically 57 squash accessions collected in seven departments of the Caribbean region of Colombia, which are part of the germplasm collection of the Corporación Colombiana de Investigación Agropecuaria – AGROSAVIA. The experiment was established under a completely randomized design at the Caribia Research Center located in the Zona Bananera municipality, Magdalena, Tropical Dry Forest (bs-T) life zone. From each of the accessions, 13 qualitative descriptors and 18 quantitative descriptors were evaluated. For the quantitative variables, a principal component analysis was performed to determine the characteristics with the greatest contribution to the total variability and to identify groups of genotypes. For the qualitative variables, a multiple correspondence analysis was performed. From the morphological descriptors, were determined three groups conformed for 10, 14 and 33 accessions, the first group included accessions from five departments, the second from six and the third from all departments. The groups two and three are of interest because in them were grouped the accessions with higher values for the variables weight and number of fruits, which are associated with high yield. The variables associated with yield, leaf length and width, and crop phenology explained more than 50 % of the data set in the first three principal components.